STRATEGI KOMUNIKASI DINAS PARIWISATA DAN KEBUDAYAAN DALAM MEMPROMOSIKAN DESTINASI WISATA DI KABUPATEN ROKAN HULU - Bolantara, Dwiki; Yozani, Ringgo Eldapi (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
The communication strategy that has been implemented by the Tourism and Culture Office of Rokan Hulu Regency in promoting tourist destinations in Rokan Hulu Regency has not implemented optimally. This can be seen from the many tourist destinations, there are only four tourist objects that can attract many tourist to visit and contribute to lacal revenue. To see the communication strategy that has been carried out, the purpose of this study was to identify and analyze the strategy of the Tourism and Culture Office of Rokan Hulu Regency in installing communicators, messages, media and targets to promote tourist destinations in Rokan Hulu Regency. The research method used is qualitative with a descriptive approach. The informants in this study came from two elements, namely local government and tourists. The selection of informants used a purposive technique with the criteria of informants being people who know best about the implementation of strategic communication in promoting tourist destinations in Rokan Hulu Regency and people who have known and visited tourist destinations in Rokan Hulu Regency. Data collection was carried out by means of observation, interviews and documentation. The results of the study indicate that strategic communication carried out by the Tourism and Culture Departement of Rokan Hulu Regency in promoting tourist destinations has not gone well. The appointment of Bujang and Dara Rokan Hulu as brand ambassadors in promoting tourist destinations has not been fully able to lift the very many tourist destinations in Rokan Hulu Regency. The message strategy implemented has been going well, it's just that the content of the messages conveyed is not good yet, because there is still a lack of information provided regarding other supported tours. The media selection strategy used is appropriate, but the management of social media as a promotional medium is not good, so that many of the target groups do not choose social media as promotional media. The strategy in setting targets is also considered appropriate, namely by making observations and developments based on data on tourist visits. Keywords: strategy, communication, tourist destinations